CHEST COMPUTED TOMOGRAPHY SEVERITY SCORING AND ITS RELATION WITH AGE AND GENDER DURING THE SECOND WAVE OF COVID-19 PANDEMIC – A RETROSPECTIVE AND OBSERVATIONAL STUDY - BIKASH PARIDA; SUMITA SWAIN; SOUMYA SAMAL; SATYA SUNDAR GAJENDRA MOHAPATRA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Our study aimed to assess the lung involvement using computed tomography (CT) severity scores and to determine how age and gender affect the severity of infection during the second wave of COVID-19. Methods: This retrospective and observational study was conducted in a dedicated COVID hospital. A total of 650 positive patients who gave their consent were included in this study. The CT severity score (25 points) was categorized as mild (<7), moderate (7–18), and severe (>18). Results: Patient’s age of 10–86 years with a mean and SD was 47.77±15.21 years, of which 440 were male and 210 were females. Males were more significantly affected than females (p=0.007). The mean±SD of CT severity score was 8.69±6.28, and ranging from 0 to 25. The most affected age group in the second wave of COVID-19 was 41–60 years (275 patients, 42.3%). A significant positive correlation between total CT severity with age, but it was mild (r=0.16, p=0.003). Conclusion: The age range with the highest CT severity score and the majority of men was 41–60 years. In addition, there was a strong association between the severity of the CT and both male gender and age.